2018
DOI: 10.1080/09712119.2018.1496920
|View full text |Cite
|
Sign up to set email alerts
|

Fescue toxicosis and its influence on the rumen microbiome: mitigation of production losses through clover isoflavones

Abstract: This review highlights concerns with endophyte-infected tall fescue as a primary forage base in the southeastern United States and discusses specific physiological and ruminal effects caused by consumption of ergot alkaloids. Additionally, in an effort to promote various mitigation strategies to abate production limitations caused by fescue toxicosis, this review discusses the use of cool-season legumes, specifically red clover, with the already established forage base. Clovers are often mixed into pastures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Feed with mycotoxins or other potentially harmful substances have been shown to influence the rumen microbiota ( 16 ). In the current research, toxins in tall fescue affected alpha-diversity measures such as the number of observed OTUs and Shannon diversity index.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Feed with mycotoxins or other potentially harmful substances have been shown to influence the rumen microbiota ( 16 ). In the current research, toxins in tall fescue affected alpha-diversity measures such as the number of observed OTUs and Shannon diversity index.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin homeostatic levels are sensitive to tall fescue toxins and are a measure of the degree of tall fescue mycotoxicosis ( 37 ). Since ergovaline has a ring structure similar to the major prolactin inhibitor (dopamine), this may significantly affect serum prolactin concentration ( 16 ). In the current study, serum prolactin levels were not statistically different between treatments; however, numerically lower values were observed in MA treatment on d115.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New data from our lab [ 67 , 68 , 69 ], among other recent reports [ 38 , 70 , 71 ], indicate that developing integrative interactomics-based approaches to complement other, more traditional methods for evaluating the livestock integrome could increase our understanding about the development and adaptive versus pathophysiological responses to one of the costliest diseases to the United States beef industry, fescue toxicosis. The rest of this review will focus on introducing what we currently know about fescue toxicosis development and pathophysiology and how newly generated ‘omics data could be integrated to help fill crucial knowledge gaps related to this disease.…”
Section: Maintaining Animal Productivity and Wellness In Adverse Ementioning
confidence: 99%